(untitled) (REMUNOM, 2024)
The objective of this study was to compare the fluoride release rate from Conventional Glass Ionomer Cement (GIC) and Photoactivated Glass Ionomer Cement, as well as infer the influence of the surface protection of the material with cavity varnish on this release. Using an in vitro methodology, a total of 84 specimens were divided into two groups: Group 1 (GICC) and Group 2 (GICP). Three subgroups (n=14) were created for each group: for conventional cements - Sample A (Vidrion R), Sample B (Vitro Fil), Sample C (Maxxion R), and for light-activated cements - Sample D (FIL FIL LC ), Sample E (Riva LC) and Sample F (Ionoseal). After complete polymerization of the specimens, half of the samples from each subgroup (7 samples) received surface protection with cavity varnish (Cavitine -SSWHITE). To compare the release of fluoride between materials, the Student’s t-test was applied for independent groups. To determine whether there were significant differences in fluoride release over time, the repeated measures ANOVA test with multiple comparisons using Bonferroni adjustment was used. The greatest release of fluoride for varnish-coated materials occurred after 28 days (GICC = 27.97 ± 28.12; GICP = 15.73 ± 11.25). For GICs without varnish application, the greatest release of fluoride occurred after 21 days (GICC = 21.33 ± 19.65; GICP = 15.37 ± 16.68). No statistically significant differences were observed between the groups evaluated (p > 0.05). It was possible to conclude that GICs release fluoride at different time intervals and the surface protection of the cements did not negatively impact the release of fluoride from the analyzed materials.